2021
DOI: 10.1039/d0ra09640g
|View full text |Cite
|
Sign up to set email alerts
|

Iodonium salts as efficient iodine(iii)-based noncovalent organocatalysts for Knorr-type reactions

Abstract: The dibenziodolium cation displays high catalytic activity for the Knorr-type reactions via binding with the carbonyl O atom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(68 citation statements)
references
References 77 publications
3
55
0
Order By: Relevance
“…The S-shape of the kinetic curves is caused by the initial accumulation of the intermediate. 41 Fig. 3 The molecular structure of [5]OTf determined by X-ray diffraction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The S-shape of the kinetic curves is caused by the initial accumulation of the intermediate. 41 Fig. 3 The molecular structure of [5]OTf determined by X-ray diffraction.…”
Section: Methodsmentioning
confidence: 99%
“…The generation of 1-benzoyl-3,5-dimethylpyrazole from acetyl acetone and benzoyl hydrazide (Knorr-type reac-tion; Scheme 2) was selected as the model reaction for the experimental confirmation of the theoretical data because it involved carbonyl activation and was deemed suitable in our group's previous study regarding the catalytic activity of iodine (III) derivatives. 41 Proton nuclear magnetic resonance ( 1 H-NMR) monitoring indicated that the most active species for the test reaction was the triazolium [7]OTf, and the imidazolium [6]OTf was less active (Fig. 4).…”
Section: Experimental Confirmation Of the Relative Catalytic Activity Of The Studied Azoliumsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to these typical XB model reactions involving neutral substrate activation, the catalysis of Knorr‐type reactions between acetylacetone and acyl hydrazides using iodolium 17 a was published recently by Bolotin and coworkers (Scheme 13). [105] Therein, it was shown that using 17 a salts (as OTf, TFA and NTf 2 salts) provided sufficient activation for the reaction to proceed. In contrast, neutral non‐hypervalent XB donors, as well as other iodine(III) compounds such as diphenyliodonium trifluoroacetate failed to promote the reaction.…”
Section: Applications In Organocatalysismentioning
confidence: 99%